Age dependent seizure susceptibility of CA2 hippocampal neurons - Correa, Jeff; Sablani, Shashank; Wasfi, Michael; Correa, Chris; Bandelow, Stephan (Frontiers in Cellular Neuroscience, 2025)
The hippocampal CA2 region is increasingly recognized as a functionally distinct subfield essential for social recognition memory and the proper routing of information through the hippocampal circuit. Unlike the CA1 and CA3 subfields, CA2 pyramidal neurons show relative sparing from seizure-associated cell loss in many adult models of epilepsy; however, this resilience is not absolute, as recent work demonstrates that CA2 can also exhibit heightened excitability and contribute to seizure propagation under certain models and pathological conditions. Multiple cellular and molecular features—including dense inhibitory interneuron networks, enriched expression of RGS14, PCP4, STEP, perineuronal nets (PNNs), and specialized calcium-handling machinery—collectively constrain synaptic plasticity and reduce excitotoxic vulnerability in mature CA2 neurons. In contrast, these protective mechanisms are underdeveloped during early postnatal periods, rendering the CA2 region more susceptible to hyperexcitation and circuit disruption. Early-life seizures (ELS) occurring within this developmental window may therefore adversely reshape CA2 connectivity and function, potentially altering social memory formation and contributing to later-life cognitive or behavioral impairments. Understanding how CA2 transitions from early vulnerability to adult resilience provides a critical framework for linking developmental epileptogenic insults to long-term deficits in social and mnemonic processing.